Ethnoveterinary study of plant resources of Takht Bhai, Mardan, Khyber Pakhtunkhwa, Pakistan - Awais Shah, Syed; Adil, Muhammad; Ullah, Hamid; Muhammad , Adil (Ethnobotany Research and Applications, 2024)
Background: This ethnoveterinary medicine study conducted in Takht Bhai investigates plant-based remedies for animal diseases, acknowledging the significant role animals play in the environment. Local residents possess substantial knowledge of medicinal plants. Methods: Ethnoveterinary data were obtained through interviews, observations and questionnaires in 2018-2019, with a primary focus on documenting plant habits, local names, ethnoveterinary uses and the plant parts employed for treating animal diseases. Results: A total of 79 plants from 46 different families were collected, dried, and preserved on herbarium sheets, encompassing 47 herbs, 26 trees, 4 shrubs, and 2 climbers. Various plant parts were analyzed, including leaves from 26 plants, bark from 5 plants, roots from 2 plants, oils from 2 plants, tubers from 1 plant, stems from 1 plant, and rhizomes from 2 plants. Additionally, 5 complete plants were utilized for treating various ailments. Herbs demonstrated particular efficacy in addressing severe illnesses such as hepatitis, diarrhea, mastitis, bleeding, gastrointestinal issues, mouth and foot tympany, and gas. Local residents utilized diverse plant parts, such as leaves, fruits, seeds, barks, and rhizomes, to prepare medicinal remedies. Conclusions: The ethnoveterinary study conducted in Jalala, Mad-e-Baba, and Takkar underscores the potential of indigenous flora for promoting livestock health. This knowledge holds promise for informing sustainable healthcare solutions tailored to rural communities reliant on livestock. Keywords: Ethnoveterinary; Medicinal plant, Rural communities; Livestock, Animal diseases.